Flexibility and environmental assessment of process-intensified design solutions: A DWC case study. (March 2022) - Di Pretoro, Alessandro; Fedeli, Matteo; Ciranna, Flavia; Joulia, Xavier; Montastruc, Ludovic; Manenti, Flavio
Highlights: Process intensified solutions results to be more profitable and sustainable but their design is usually optimized with respect to nominal operating conditions only. In case of bio-processes accounting for external deviations is of critical importance due to the feedstock nature fluctuations over the seasons. A preliminary flexibility assessment during the design phase allows to identify the best design configuration corresponding to different flexibility requirements. Abstract: During the last decades, energy and process integration have become the most spread practices to optimize chemical processes both from economic and environmental perspectives. While the design of the integrated and conventional configurations are usually compared by referring to nominal operating conditions, assessing the implications of process integration on system flexibility could be of critical importance, especially when considering the uncertain nature of renewables. This paper aims then at the comparison of different integrated and conventional unit design performances under uncertain conditions by means of a biorefinery Acetone-Butanol-Ethanol separation case study. An indirect distillation train and different configurations of Dividing Wall Column have been designed and compared to assess the environmental and economic advantages for different flexibility ranges. The proposed methodology allows to select the most suitable configuration for the required performance and to have more conscious expectations about investment costs and emissions when flexibility is taken into account.